2008
DOI: 10.19030/jdm.v3i4.4999
|View full text |Cite
|
Sign up to set email alerts
|

The Influence Factors That Affect Thailands Management Of Youth Reproductive Health Service

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…The nding is consistent with Cheptum, et al [29] who reported that lack of facilities, inadequate sta ng and negative staff attitude were associated with access and use of health services. Anusornteerakul, Khamanarong, Khamanarong, and Thinkhamrop [30] reported that health service system is one of the important factors in uencing management of youth's reproductive health services.…”
Section: Discussionmentioning
confidence: 99%
“…The nding is consistent with Cheptum, et al [29] who reported that lack of facilities, inadequate sta ng and negative staff attitude were associated with access and use of health services. Anusornteerakul, Khamanarong, Khamanarong, and Thinkhamrop [30] reported that health service system is one of the important factors in uencing management of youth's reproductive health services.…”
Section: Discussionmentioning
confidence: 99%
“…The nding is consistent with Cheptum, et al [27] that lack of facilities, inadequate sta ng and negative staff attitude were associated with access and use of health services. Anusornteerakul, Khamanarong, Khamanarong, and Thinkhamrop [28] reported that health service system is one of the important factors in uencing management of youth reproductive health services.…”
Section: Discussionmentioning
confidence: 99%
“…The nding is consistent with Cheptum, et al [29] who reported that lack of facilities, inadequate sta ng and negative staff attitude were associated with access and use of health services. Anusornteerakul, Khamanarong, Khamanarong, and Thinkhamrop [30] reported that health service system is one of the important factors in uencing management of youth reproductive health services.…”
Section: Discussionmentioning
confidence: 99%